PERANCANGAN MONITORING SYSTEM UNTUK PHARMACEUTICAL REFRIGERATOR MENGGUNAKAN SENSOR DHT22-MQ9 BERBASIS IOT - Maulana, Irfan Maulana; Haryanti, Tri (Politeknik Negeri Indramayu, 2025)
The quality of pharmaceutical storage is highly influenced by temperature stability, humidity, and environmental cleanliness. Suboptimal monitoring of pharmaceutical refrigerators can lead to the degradation of active drug ingredients and reduce efficacy. This study aims to design, develop, and evaluate an Internet of Things (IoT)-based Smart Monitoring System for pharmaceutical refrigerators. The system integrates DHT22 and MQ-9 sensors using NodeMCU ESP8266 and the Arduino IoT Cloud platform to monitor temperature, humidity, and the presence of harmful gases in real-time, ensuring drug storage stability. Calibration was performed by comparing sensor readings against the Elitech GSP-6 reference measuring device and the safe threshold standard for carbon monoxide (200 ppm). Test results showed that DHT22 temperature readings ranged from 8–13°C (a deviation of +1–2°C from the reference), while humidity readings were 50–82% (a deviation of -2–3% from the reference). The minimum temperature only reached 8°C (failing to achieve the target of 2°C) due to door-opening activity and refrigerator overloading. The MQ-9 sensor recorded safe CO concentrations (22–42 ppm, equivalent to 11–21% of the 200 ppm limit). CO gas fluctuations remained within tolerance limits, but temperature and humidity occasionally exceeded WHO and BPOM standards (temperature: 2–8°C; humidity: 40–60%). The system provides accurate and responsive monitoring, supporting improved efficiency in automated pharmaceutical storage environment supervision, and has the potential to prevent product degradation due to unsuitable storage conditions.